Wine, beer, mead... Social and cultural aspects of alcohol consumption at the Jagiellonian courts around 1500 - Petr Kozák (Historický Časopis, 2023)
This study presents a probe into the field of beverage culture as it was cultivated in the late 15th and early 16th century at the courts of the descendants of Casimir IV († 1492) ruler of Poland and Lithuania of the Jagiellonian dynasty: King Vladislaus († 1516) of Bohemia and Hungary, his son, King Louis († 1526) of Bohemia and Hungary, and then his brothers, King John Albert († 1501) of Poland, the Grand Duke of Lithuania and later also King of Poland Alexander († 1506) and the future ruler of Poland-Lithuania (the then Duke of Opava and Głogów and the governor of Silesia and Lusatia) Sigismund († 1548). The starting point of the research was a comprehensive analysis of rare, preserved account books kept at the courts of these monarchs. This study describes the various types of beverages consumed (especially wine and beer) both in the social and geographical contexts. In addition, it also includes the sphere of consumers’ taste preferences.